Penerapan Pembelajaran Permainan Olahraga Tradisional Hadang Terhadap Tiga Aspek Kognitif Afektif dan Psikomotor pada Peserta Didik Kelas VII di SMP IT Najib Rasyid - Bhakti, Rico; Nurdiansyah, Dani (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the application of traditional hadang sports games in physical education learning and their influence on the cognitive, affective, and psychomotor aspects of students. The research method used was Classroom Action Research (CAR) with a peer teaching model and the JWAB (Total Active Learning Time) instrument. The research subjects were 29 seventh-grade students at SMP IT Najib Rasyid. Data were collected through pre-tests, post-tests, observations, and documentation, and then analyzed using triangulation of sources, time, and techniques. The results of the study indicate that the implementation of traditional hadang games can gradually improve cognitive, affective, and psychomotor skills from the pre-cycle, cycle I, to cycle II. The improvements achieved were significant, with 100% of students able to understand and master the game techniques as instructed. These findings indicate that traditional hadang games are not only effective in improving motor skills but also foster cooperation, sportsmanship, and active student engagement in learning. Thus, traditional hadang games can serve as an alternative strategy for physical education that is both enjoyable and supportive of children's social skill development.